Going ‘meta’: a systematic review of metacognition and functional neurological disorder - Sadnicka, A; Strudwick, A; Grogan, JP; Manohar, S; Nielsen, G (Oxford University Press, 2025)
In functional neurological disorder (FND), there is a fundamental disconnect between an apparently intact nervous system and the individuals’ ability to consistently perform motor actions, perceive sensory signals and/or access effective cognition. Metacognition, the capacity to self-evaluate cognitive performance, appears highly relevant to FND pathophysiology. Poor metacognition is a potential mechanism via which abnormal models of self and the state of the world could arise and persist unchecked. There is therefore a justified enthusiasm that studies of metacognition may give substance to FND’s intangible nature. However, many assume an impairment in metacognition even though experimental studies are still in their infancy. This systematic review provides an analytical checkpoint of the evidence after the first five years of experimental work. We firstly summarize current methods for testing metacognition, prerequisite knowledge that allows readers to independently evaluate the evidence. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we then screened the 21 articles on this topic and review the experimental data of the eight studies that specifically tested metacognition in subjects with FND. Questionnaire metrics used to estimate global metacognition and general confidence in FND revealed a mixed picture of low or normal confidence. Of the five studies that used performance-controlled metrics, the gold-standard to estimate local metacognition in FND, four found metacognition to be equivalent to healthy controls and one paper supported impaired metacognition. We consequently try and broaden the debate and discuss alternative headline scenarios. We review how positive studies may offer insight and debate whether null studies could represent false negatives. However, since most studies find equivalent metacognition to controls, we also discuss whether metacognition could be intact and how this could inform mechanistic models of FND and have potential clinical utility. In summary, this review highlights signal of interest within the data, exposes current limitations and flags the many open questions.